EVALUATION OF HEPATOPROTECTIVE, ANALGESIC AND ANTIPYRETIC ACTIVITY OF AQUEOUS EXTRACTS OF BOERHAAVIA DIFFUSA AND ANISOCHLILUS CARNOSUS - VENKATESH P; DINAKAR A; SENTHILKUMAR N (International Journal of Pharma and Bio Sciences, 2013)
An aqueous extracts of stem and leaves of Boerhaavia Diffusa (Aq.EBD) and leaves of Anisochilus Carnosus (Aq.EAC) was studied for hepatoprotective, analgesic and antipyretic activity. Hepatotoxicity was introduced in Albino rats of either sex by intraperitoneal injection of CCl4 (in olive oil). Tail immersion method and Hot plate method in mice were studied for analgesic activity, Yeast induced pyrexia method in rats was followed to evaluate antipyretic activity. Aq.EBD and Aq.EAC were administered to the experimental animals at the dose levels 150mg and 300mg/kg body weight, 200mg and 400mg/kg body weight of Aq.EBD and Aq.EAC respectively. The hepatoprotective effects of the extracts were evaluated by the assay of liver function biochemical parameters like Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyruvate Tranaminase (SGPT), Serum Alkaline Phosphatase (SALP), Total and Direct Serum Bilirubin. It was concluded that, the Aq.EBD and Aq.EAC possess hepatoprotective activity against CCl4 induced hepatotoxicity in rats, in both analgesic methods the extracts has shown significant activity and the dose was also shown significant results for antipyretic activity.